2011
DOI: 10.1007/s10518-011-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of site effects in the Aterno river valley (Central Italy) from aftershocks of the 2009 L’Aquila earthquake

Abstract: A temporary network of 33 seismic stations was deployed in the area struck by the 6th April 2009, Mw 6.1 (Scognamiglio et al. in Seism Res Lett 6/81, 2010), L'Aquila earthquake (central Italy), with the aim to investigate the site amplification within the Aterno river Valley. The seismograms of 18 earthquakes recorded by 14 of the 33 stations were used to evaluate the average horizontal to vertical spectral ratio (HVSR) for each site and the 123 698 Bull Earthquake Eng (2011) 9:697-715standard horizontal spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…As already observed by other authors Bergamaschi et al 2011), the empirical functions found in this study confirm the large variability of the site response in the Abruzzo region that cannot be taken into account using simple site-classification based on geological information (Table 1). Furthermore, this study also confirms the relevance of the amplification on the vertical motions, indicating that in the L'Aquila region, the H/V ratio should be used with caution for evaluating the local site response.…”
Section: Site Functionssupporting
confidence: 90%
See 2 more Smart Citations
“…As already observed by other authors Bergamaschi et al 2011), the empirical functions found in this study confirm the large variability of the site response in the Abruzzo region that cannot be taken into account using simple site-classification based on geological information (Table 1). Furthermore, this study also confirms the relevance of the amplification on the vertical motions, indicating that in the L'Aquila region, the H/V ratio should be used with caution for evaluating the local site response.…”
Section: Site Functionssupporting
confidence: 90%
“…The considered networks are: the National Seismic Network, RSN, operated by INGV (Istituto Nazionale di Geofisica e Vulcanologia); the Mediterrean Network, Mednet, operated by INGV; the Rapid Response Networks operated by INGV, RESIF (Reseau Seismologique and Geodesique Francais) and the University of Genoa; the National Accelerometric Network, RAN, operated by the Department of Civil Protection, DPC. We complete the data set by including data from temporary networks deployed for seismic microzonation (Working Group SM-AQ 2010), site effect studies (Bergamaschi et al 2011) and aftershock monitoring (Margheriti et al 2011). Details on instruments and stations of each network are listed in Table 1.…”
Section: Ata S E Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic data show that L'Aquila downtown is characterized by a clear resonance frequency at about 0.6 Hz (De Luca et al 2005;Milana et al, this issue) whereas in the Aterno river valley the fundamental frequencies can increase up to 5 Hz (Bertrand et al 2009;Bergamaschi et al 2011).…”
Section: The Study Areamentioning
confidence: 94%
“…2). The seismic stations considered in this paper were installed for the evaluation of local amplification phenomena (Bergamaschi et al 2011) as well as in the framework of a national project (C.A.S.E project, where C.A.S.E stands for Anti-seismic, Sustainable and Environment-Friendly Buildings) aimed at the construction in the epicentral area of seismic-isolated buildings. Although the three villages are within a distance of 2 km from each other and the historical masonry buildings are supposed to share the same quality and characteristics, they suffered a different degree of damage (Galli and Camassi 2009).…”
mentioning
confidence: 99%